VEGF Receptor 1 Promotes Hypoxia-Induced Hematopoietic Progenitor Proliferation and Differentiation - Florentin, Jonathan; O’Neil, Scott P.; Ohayon, Lee L.; Uddin, Afaz; Vasamsetti, Sathish Babu; Arunkumar, Anagha; Ghosh, Samit; Boatz, Jennifer C.; Sui, Justin; Kliment, Corrine R.; Chan, Stephen Y.; Dutta, Partha (Frontiers in Immunology, 2022)
Although it is well known that hypoxia incites unleashed cellular inflammation, the mechanisms of exaggerated cellular inflammation in hypoxic conditions are not known. We observed augmented proliferation of hematopoietic stem and progenitor cells (HSPC), precursors of inflammatory leukocytes, in mice under hypoxia. Consistently, a transcriptomic analysis of human HSPC exposed to hypoxic conditions revealed elevated expression of genes involved in progenitor proliferation and differentiation. Additionally, bone marrow cells in mice expressed high amount of vascular endothelial growth factor (VEGF), and HSPC elevated VEGF receptor 1 (VEGFr1) and its target genes in hypoxic conditions. In line with this, VEGFr1 blockade in vivo and in vitro decreased HSPC proliferation and attenuated inflammation. In silico and ChIP experiments demonstrated that HIF-1⍺ binds to the promoter region of VEGFR1. Correspondingly, HIF1a silencing decreased VEGFr1 expression in HSPC and diminished their proliferation. These results indicate that VEGF signaling in HSPC is an important mediator of their proliferation and differentiation in hypoxia-induced inflammation and represents a potential therapeutic target to prevent aberrant inflammation in hypoxia-associated diseases.